Assessing Economic Inclusivity in Sumatra: A Miyazawa Input-Output Table Analysis, 2022 - Murjani, Ahmad; Ramadhan, Muhammad Febrian Rizky; Santoso, Dimas Hari; Rusyiana, Aris (Jurnal Ekonomi-Qu, 2025)
Good development is distinguished by not solely pursuing perpetual growth but also by providing positive impacts that are accessible to every stratum of society. This research aims to determine whether Sumatra's economy in 2022 has yielded equitable income distribution across all layers of society, particularly when examined in-depth in each economic sector. By utilizing Miyazawa's input-output table analysis, we obtained several significant findings. The Manufacturing Industry emerged prominently as Sumatra's financial backbone and critical sector. Furthermore, out of the 17 industries, there are 9 inclusive sectors, 2 of which are vital, namely the Manufacturing Industry and the Transportation and Storage. Lastly, Other Services Activities significantly influence the income of the lower 40 percent bracket.